PICKING ‘MANTEN TEBU’ CANE IN THE SYNCRETISM OF THE CEMBENGAN TRADITION PERSPECTIVE OF VALUE EDUCATION AND URF' - Lila Pangestu Hadiningrum; Siti Rokhaniyah; Ning Karnawijaya (International Conference on Social and Islamic Studies, 2021)
In facing the era of openness of society 5.0, an ethical filter is needed with an effort to give meaning to the aesthetic values ​​that are assets of national culture. Value education and 'urf are one of the counter hegemony in the millennial era. The flow of industrialization brings consequences for social change. The existence of a traditional religious system has its own charm. This phenomenon can be seen in the syncretism of the cembengan tradition that took place in sugar factories on the island of Java, especially in this study in Solo Raya. This study aims to describe the history, implementation of picking ‘manten tebu’ cane and the relevance of picking ‘manten tebu’ cane in the syncretism of the Cembengan tradition in terms of value education and 'urf. This research is field research using primary and secondary data, and Milles and Huberman model analysis techniques. The results of this study show that the harmony of the community around the sugar factory in Solo Raya as a multicultural society can be seen from the ritual symbols and spiritual symbols in the Cembengan tradition which contains syncretism between Confucianism-Islam-Javanese which is integrated into mystical cultural discourse. The phenomenon of the procession of marrying ‘tebu’ cane/cembengan in the procession of the cane ‘manten tebu’ carnival is followed by the ijab qobul led by the penghulu who in this case is represented by the traditional leader and the procession ends with a sukur (the distribution of each ubo rampe). The value education of picking ‘manten tebu’ cane in the synchronization of the cembengan tradition can be seen from religious values ​​and social values. When viewed from the implementation, it includes 'urf fi'li but from its scope it is 'urf Khash because it is only carried out by sugarcane farmers around the sugar factory. And in terms of assessment, it is urf shohih if the belief or belief in carrying out the tradition continues to ask God and will become 'urf fasid if there is a misunderstanding and causes damage to aqidah if it is done to ask the unseen ruler.